Implementasi dan Analisis Purwarupa Sistem Collision Avoidance pada Mobil Pintar Berbasis Jaringan Sensor Nirkabel [Implementation and Analysis Prototype of Collision Avoidance System in Smart Car Based on Wireless Sensor Network] - Dwi Kresna Wijaya; Doan Perdana; Yoseph Gustommy Bisono (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2017)
Accidents are the third highest cause of death in the world. Through the collision avoidance system applied to smart car, it is expected that accidents on the car can be avoided and the number of accidents can be reduced. This system applies the concept Wireless Sensor Network (WSN), the type of network that can pass through the process of sensing, transmitting data, and monitoring through internet connection. The design and implementation of collision avoidance prototype in this smart car works by means of the distance between the cars obtained from the Ultrasonic HC-SR04 sensor which then becomes the Arduino Uno input to regulate the speed of the car in order to avoid a collision. Communication between cars using Xbee S2 is connected to Raspberry Pi to connect to the web server. Information gained distance and speed of the car will occur on websites that can be accessed by the user. Maximum Xbee S2 test result are 89 meters. The delay value from the sensor to the monitoring system is 0.411 second, while the average throughput value is 641.73 bytes/s *****Kecelakaan menjadi penyebab tertinggi ketiga kematian di dunia. Melaui sistem collision avoidance yang diterapkan pada mobil pintar, diharapkan agar kecelakaan pada mobil dapat terhindarkan dan angka kecelakaan dapat berkurang. Sistem ini menerapkan konsep Wireless Sensor Network (WSN), jenis jaringan yang dapat melalukan proses sensing, pengiriman data, serta monitoring melalui koneksi internet. Perancangan dan implementasi purwarupa collision avoidance pada mobil pintar ini bekerja dengan cara mendapatkan jarak antar mobil yang didapat dari sensor Ultrasonik HC-SR04 yang kemudian menjadi input Arduino untuk mengatur kecepatan optimal mobil agar tidak terjadi tabrakan. Komunikasi antar mobil menggunakan Xbee S2 yang dihubungkan ke Raspberry Pi untuk dikoneksikan ke web server. Informasi yang didapat berupa jarak dan kecepatan mobil akan ditampilkan pada website yang dapat diakses oleh pengguna. Hasil pengujian didapatkan jangkauan maksimal Xbee S2 adalah 89 meter. Nilai delay dari sensor hingga sistem monitoring didapatkan rata-rata 0,411 detik, sedangkan nilai throughput rata-rata adalah 641,73 bytes/s.